Robust phase locked loop for grid synchronization of distributed power generation systems - Lee, Beng Chuan (2016)
This report studies the robustness of a single phase second order generalized integrator (SOGI) type of Phase Locked Loop (PLL) through simulation using Matlab and Simulink. Suggestions were made to reject dc offset due to quantization and also improve the harmonic rejection ability of SOGI-PLL by using notch filters to remove the even order harmonics, generated during the process of tracking within the SOGI-PLL system. Due to rapid climate change and increasing need for electricity consumption, the need to incorporate renewable energy to the power grid network is on a rise. In addition, renewable power source can also help to improve the performance of power system by compensating the reactive power and it may also reduce the frequency variation. However, power electronics in the renewable power source may cause high voltage distortion in the grid. Hence, high harmonic rejection ability PLL is needed. PLL is needed for proper grid synchronization by providing accurate estimation of grid voltage amplitude and phase angle for the grid-tied inverter to provide correct active and reactive power flow. Since PLL can be seen as a control system to track the two voltage parameters hence study of PLL tuning method can also be found in this report. According to the study, even order harmonics in the SOGI-PLL system are the main contributor to inaccurate estimation. And result in this report had shown that using two set of notch filters can eliminate the inaccuracy. However, this modified SOGI-PLL had not been experimented yet. In addition, future work is needed to make the notch filter adaptive so as to ensure consistent high performance for this modified SOGI-PLL. In short, SOGI-PLL can provides fast and accurate tracking by adding two set of notch filters to remove even order harmonics generated by the polluted voltage signal in the grid based on Matlab and Simulink simulation result. Future works can be done to verify this simulated result and improvement on notch filter can provides more optimum result.